Quality of Life Comparisons in Strabismic Children Managed Surgically or Conservatively: Oral Presentation - Observational Study - Resident - ESTER GRACESILLYA APRINONA G; Maya Sari Wahyu Kuntorini, MD; Elsa Gustianty, MD; Feti Karfiati Memed, MD; Irawati Irfani, MD; Primawati Oktarima Amiruddin, MD; Sesy Caesarya, MD (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction & Objectives : Strabismus causes visual impairment due to ocular misalignment, interferes cosmetic appearance, results in negative self-image and impacts quality of life. Studies in adults have shown that successful strabismus surgery improves quality of life, but awareness of strabismus surgery and its benefits are still lacking. Studies regarding the impact of conservative treatment on quality of life are limited, so further study is required. Methods : This was an observational study comparing 2 unpaired groups. The method used in this study was cross-sectional and samples were obtained purposefully according to medical records and consecutively based on outpatient visits. Results : Thirty-six subjects in group A, who had undergone strabismus surgery and 33 subjects in group B who were still managed conservatively were included in this study. Both groups had similar demographic characteristics, except parental education background (p=0.048). Comparative test of2 unpaired groups in this study showed higher quality of life scores in group A (p=0.0001). Conclusion : The quality of life in subjects who had undergone strabismus surgery was better than that in those who were still managed conservatively.